Decrypting the layers of Entrepreneurship: A Contemplation of Business Skills in Select Children’s Classics - Devika T.S.; Sreena K. (Communications of International Proceedings, 2021)
The transformation and momentum of today prominently necessitated by the technological revolution urge an uncompromising resetting of current objectives of education that enable children to walk with the demands of the ever-changing scenario for survival and well-being. The unique capability of literature in influencing the belief systems and thought processes of kids has unquestionably proved beyond ages and children’s literature thus became a validated source of enlightening them with life lessons that guide them to move forward in midst of any adversity. However, Entrepreneurship and its surging significance as an inexorable life skill have often being ignored in present educational system especially in the preliminary level where children are molded to become productive citizens of tomorrow. Fortunately, though less in number in comparison, gallant attempts have been made in fiction intended for children to nurture entrepreneurial qualities in them which can serve as an effective substitute to the lack of their inclusion in present educational scenario. The paper undertakes to trace the possible positive impacts of such literature for children in general as well as in specific with reference to selected texts that seem to provide important business lessons veiled in interested stories so that children learn those skills unintentionally while being immersed in the tremendous joy of the fictional world these books grant. The research design uses the methodology of textual analysis by attempting to interpret two well-known children’s classics that have miraculously depicted some essential qualities expected from an entrepreneur simultaneously retaining the quality of fiction both in theme and language.
Keywords: Entrepreneurship; Business; Children’s Literature.